الرمز الشعري الصوفي : نشأته و أنواعه و تطوره حتى القرن السابع الهجري - مشارة, حسين (جامعة الوادي - university of Eloued, 2022)
شهد الإبداع الصوفي هزات عنيفة في مختلف مراحل تاريخه ، و من أبرزها حادثة مقتل الحلاج التي تركت أثرا بالغا في حركة الإبداع الشعري ، حيث توجه الشعراء من بعده إلى البحث عن الأداة الفنية الأقدر على التوسط بين الإعلان الشعري و كتمان التجربة الصوفية ، و لم يجدوا أفضل من الرمز الشعري بكل ما فيه من طاقات التركيز و العمق ، فهو الوسيلة اللغوية التي استطاعوا أن يعبروا بها عما في عوالمهم من إثارة و سمو و مجاهدة ، عن طريق خمسة أنواع من الرموز و هي : المرأة و الخمر و المكان و العدد و الحرف ، و قد فتحت مجالا رحبا عند شراح الشعر لبيان معانيها و تأويلها وفق ما جمعه علماء التصوف من المعارف الفقهية و اللغوية و الفلسفية . Sufi creativity has witnessed violent shocks in various stages of its history, notably the killing of Al Hallaj, which left a great impact in the movement of poetic creativity, where the poets went after him to search for the best technical tool to mediate between the poetic declaration and the secrecy of Sufi experience, Of the poetic symbol with all the energies of concentration, depth and inspiration, it is the language means that they were able to express what in their worlds of excitement and splendor, through five types of symbols namely: women, wine, place, number and character, and Has opened up a wide area when the poetry of poetry to explain their meanings and interpretation as collected Sufism scholars of jurisprudence knowledge and linguistic and philosophical.
مقال
Keywords: الرمز ؛ الشعر الصوفي ؛ النشأة؛ القرن السابع الهجري